A systematic review of system dynamics and agent‐based obesity models: Evaluating obesity as part of the global syndemic. (17th July 2019) - Morshed, Alexandra B.; Kasman, Matt; Heuberger, Benjamin; Hammond, Ross A.; Hovmand, Peter S.
Summary: The problem of obesity has recently been reframed as part of the global syndemic— the co‐occurring, interacting pandemics of obesity, undernutrition, and climate change that are driven by common underlying societal drivers. System science modeling approaches may help clarify how these shared drivers operate and the best ways to address them. The objective of this paper was to determine to what extent existing agent‐based and system dynamics computational models of obesity provide insights into the shared drivers of the global syndemic . Peer‐reviewed studies published until July 2018 were identified from Scopus, Web of Science, and PubMed databases. Thirty‐eight studies representing 30 computational models were included. They show a growing use of system dynamics and agent‐based modeling in the past decade. They most often examined mechanisms and interventions in the areas of social network‐based influences on obesity, physiology and disease state mechanics, and the role of food and physical activity environments. Usefulness for identifying common drivers of the global syndemic was mixed; most models represented Western settings and focused on obesity determinants close to the person (eg, social circles, school settings, and neighborhood environments), with a relative paucity in models at mesolevel and macrolevel and in developing country contexts.